IMPLEMENTATION OF CUCUMBER JUICE COMPLEMENTARY THERAPY IN NURSING CARE FOR HYPERTENSION PATIENTS TO LOWER BLOOD PRESSURE AT BAKTI TIMAH HOSPITAL PANGKALPINANG IN 2026 - Aulia Roza; Shindi Hapsari (PT. Radja Intercontinental Publishing, 2026)
Hypertension is a non-communicable disease that is the main cause of various cardiovascular complications, so it requires comprehensive management, including through complementary therapy. This study aims to analyze the application of cucumber juice complementary therapy in nursing care for hypertensive patients to help lower blood pressure at Bakti Timah Hospital, Pangkalpinang. The study used a descriptive method with a case study approach. The study population consisted of 10 hypertensive patients undergoing treatment in the Marwah Room, using a total sampling technique, then 1–2 patients were selected who met the inclusion criteria as case study subjects. The research instruments included a nursing assessment format, observation sheets, evaluation sheets, nursing care documentation, medical records, and supporting examination results. Data were collected through interviews, observations, physical examinations, and documentation studies, then analyzed descriptively by comparing conditions before and after the intervention. The results showed a decrease in systolic and diastolic blood pressure, a reduction in headache complaints, and an increase in patient knowledge regarding hypertension management after administration of cucumber juice as a complementary therapy. It was concluded that cucumber juice complementary therapy has the potential to be a safe, easy-to-implement non-pharmacological nursing intervention that supports blood pressure control in hypertensive patients